Modelo não-linear para resposta imunológica - Santos, Demitry Messias (2017)
In this work, we propose a delayed nonlinear model for the dynamics of a viral infection and the immune response, based on the recent literature on the subject. We seek to have an idea about the virulence of the infection and how the immune system will act due to the non-instantaneous response of the infected individual, taking into account the evolution factor of the infectious agents and their subsequent time of perception. Using numerical routines adapted for the resolution of the model, the focus remained on its structural aspects, with analysis of the equilibrium points, bifurcations and chaotic dynamic regime.